Understanding social-ecological memory in urban agriculture: A case study from Istanbul - Alves, Susana; Başer Kalyoncuoğlu, Bahar (Mary Ann Liebert Inc., 2023)
Urban agriculture (UA) is deeply ingrained in Istanbul's sociocultural history with Bostans (historical urban vegetable gardens) serving as archetypal structures in the urban landscape. Despite the growing importance of these settings and their recognition by the United Nations Educational, Scientific, and Cultural Organization (UNESCO), planning and management of bostans has been hampered by rapid urbanization and a lack of integrative policies. This study explores the socio-ecological potential of UA practices in 10 family-related projects. Data collected through semistructured interviews, observations, and field work points to the importance of kinship in the acquisition, transmission, and modification of knowledge and practices. Farmers structure their activities based on past-present affordances and expectations for the future. This view of memory integrates social-ecological dimensions and past-present practices that offer both a forward- and backward-connecting strategy to management: backward toward greater traditional ecological knowledge and forward in terms of greater ecological and cultural resilience.
Keywords: Affordances; Culture; Heritage; Social-Ecological Memory; Urban Agriculture